Effect of Different Types of Surfectants on Zinc Efficiency in Spinach Yield - Kakar, Zia-ul-haq; Parveen, Sajida; Khattak, Sabir Gul; Saleem, Zahid (International Journal of Sustainable Agricultural Research, 2014)
A field experiment was conducted at Agriculture Research Institute Tarnab, Peshawar during 2010 to study the effect of different types of surfactants on Zinc efficiency in spinach yield and uptake of other nutrients. The experiment consisted of two different rates of Zinc Sulphate (ZnSO4) (0.5% and 1%) with three different surfactants (Aerial, Bonus and surf excel) and control without ZnSO4 and Surfactant. The experiment was laid out in RCB design with two factors having three replications. The results indicated that the effect of surfactants on Zinc efficiency had a significant effect on the yield of spinach and uptake of Potash, while Phosphorus and Zinc contents of spinach leaves were not significantly different among various treatments. Maximum yield was recorded on 1% ZnSO4 with surf excel (10.417 ton ha-1), followed by 1% ZnSO4 with Bonus, while lowest yield was recorded in 1% ZnSO4 with Aerial (7.77µg g-1) which was at par with 0.5 % ZnSO4 with Aerial, 0.5% ZnSO4 with Bonus and control. Zinc with different surfactant also significantly affected Potassium (K¬). Maximum (2.3267µg g-1) was recorded on control followed by 0.5% zinc with Aerial, which is similar with 0.5% ZnSO4 with Bonus, while minimum Potash(1.2267µg g-1) was recorded on 1% zinc with Aerial. The result of Phosphorus (P) and Zinc revealed that there were no statistically differences among difference rate of the zinc application with different surfactants. Among this 0.5% ZnSO4 with Aerial gave maximum (0.844µg g-1) of phosphorus in spinach leaves and minimum (0.7570µg g-1) was at control. Maximum zinc (0.8787µg g-1) was recorded on 0.5% zinc Sulphate, while minimum was recorded on control (0.8007µg g-1) with 0.5 % zinc with Aerial. Among various treatments used, the 1% ZnSO4 with surfactant gave maximum yield of spinach and high percentage mineral contents of spinach leaves.